A study of phonomicrosurgical arm support postures using a magnetic motion tracking system. (25th September 2015) - Chen, Ting; Vamos, Andrew C.; Dailey, Seth H.; Geng, Zhixian; Jiang, Jack J.
Abstract : Objectives/Hypothesis: To study the different arm support postures used in phonomicrosurgery by using a magnetic‐based phonomicrosurgery instrument tracking system (MPTS). Through quantitative motion parameter data collected from four arm support postures (elbow support [ES], forearm support [FS], forearm and hand support, and no support), phonomicrosurgical operation postures were analyzed and compared. Study Design: Prospective cohort study. Methods: Seven subjects operated on phonomicrosurgical simulation cutting tasks with four arm support postures while being monitored by MPTS. The motion parameters, including operation time, path length, depth perception, and motion smoothness were analyzed. The subjects' cutting quality was also calculated. Results: With the FS, the nondominant hand showed improved S, better D, and shorter P ( P < 0.05). Better motion control in the dominant hand resulted from ES posture ( P < 0.05). Better operation quality was associated with increased motion control in the nondominant hand. Conclusions: Forearm support resulted in higher steadiness and shorter surgical path in the nondominant hand. In the dominant hand, ES resulted in increased steadiness, shorter surgical path, and better D. The effect of both gravity and wrist dexterity on movement control should be considered when selecting proper arm supports. Level of Evidence: 4. Laryngoscope, 126:918–922, 2016